Review of the Book "Economics from Another View" - Vahid Moghadam; Hadi Amiri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book "Economics from Another View" by Musa Ghaninezhad is one of the few books written in Farsi in the history of economic thought. This book is written with a mental impact and with a certain intellectual orientation, which is also understandable from its title. The book is dedicated to the thoughts of 19 economists from Thomas Aquino to Douglas North, Coase, and Buchanan. The writer, in accordance with his intellectual spirit, has followed the Austrian school approach, reading the thoughts of these economists and highlighting their contributions and conflicts with this school. The book is more suitable for acquaintances with the economics and the history of economic thought and cannot be regarded as a textbook. At the same time, the author's goal is not to enter into the depths of economic thought, rather than introducing thoughts of unheard economists and their placement in the liberal tent to the audiences. The writer, in introducing the thoughts of famous economists such as Adam Smith, Marx, and Keynes, has value-judgments and he is not successful at assessing the value of their ideas in context of their time and progress of economics. Despite these critiques, the book is an influential text illustrating the views of a large body of influential economists on Iran's economic policy-making.